Intraoperative radiation therapy for colon and rectal cancers: a clinical review. Issue 1 (December 2017) - Haddock, Michael
Abstract Although there have been significant advances in the adjuvant therapy of colorectal cancer, results for patients have historically been poor when complete resection is unlikely or not possible. Similarly, locally recurrent colorectal cancer patients often experience significant tumor related morbidity and disease control and long term survival have historically been poor with standard therapies. Intraoperative radiation therapy (IORT) has been proposed as a possible tool for dose escalation in patients with locally advanced colorectal cancer. For patients with locally advanced primary or recurrent colon cancer, the absence of prospective controlled trials limits the ability to draw definitive conclusions in completely resected patients. In subtotally resected patients, the available evidence is consistent with marked improvements in disease control and survival compared to historical controls. For patients with locally advanced primary or recurrent rectal cancer, a relatively large body of evidence suggests improved disease control and survival, especially in subtotally resected patients, with the addition of IORT to moderate dose external beam radiation (EBRT) and chemotherapy. The most important prognostic factor in nearly all series is the completeness of surgical resection. Many previously irradiated patients may be carefully re-treated with radiation and IORT in addition to chemotherapy resulting in long term survival in more than 25% of patients. Peripheral nerve is dose limiting for IORT and patients receiving 15 Gy or more are at higher risk. IORT is a useful tool when dose escalation beyond EBRT tolerance limits is required for acceptable local control in patients with locally advanced primary or recurrent colorectal cancer. Previously irradiated patients should not be excluded from treatment consideration.